2011
DOI: 10.1182/blood-2010-09-308387
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF–mediated thrombopoietin release triggers neutrophil motility and mobilization from bone marrow via induction of Cxcr2 ligands

Abstract: Emergency mobilization of neutrophil granulocytes (neutrophils) from the bone marrow (BM) is a key event of early cellular immunity. The hematopoietic cytokine granulocyte-colony stimulating factor (G-CSF) stimulates this process, but it is unknown how individual neutrophils respond in situ. We show by intravital 2-photon microscopy that a systemic dose of human clinical-grade G-CSF rapidly induces the motility and entry of neutrophils into blood vessels within the tibial BM of mice. Simultaneously, the neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
175
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(190 citation statements)
references
References 40 publications
13
175
0
2
Order By: Relevance
“…At the same time, G-CSF induced thrombopoietin synthesis in the bone marrow and the ligands for CXCR2 including CXCL1 appeared to be generated by thrombopoietin stimulated megakaryocytes. 33 Recently, Bekes et al showed that tumor-associated neutrophils played a critical role in tumor angiogenesis and migration of tumor cells through secretion of TIMP-free MMP-9. 34 They also showed that the enhancement of angiogenesis was blocked by inhibition of neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, G-CSF induced thrombopoietin synthesis in the bone marrow and the ligands for CXCR2 including CXCL1 appeared to be generated by thrombopoietin stimulated megakaryocytes. 33 Recently, Bekes et al showed that tumor-associated neutrophils played a critical role in tumor angiogenesis and migration of tumor cells through secretion of TIMP-free MMP-9. 34 They also showed that the enhancement of angiogenesis was blocked by inhibition of neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…35), in the BALF of normal mice (21). In addition, 2 other Cxcr2 ligands in mice, Cxcl1 and Cxcl2, can be induced by G-CSF (4,36), implying that they may be involved in neutrophil release from BM. Whether Cxcl1 or Cxcl2 plays a role in regulating the IL-17/G-CSF axis and steady-state neutrophil homeostasis will require further investigation of their respective gene-targeted mice.…”
Section: Figurementioning
confidence: 99%
“…Neutrophil retention in the bone marrow is regulated by the coordinated action of CXCL12 and its receptor CXCR4, whereas neutrophil egress depends on CXCR2 and its ligands. 90,91 CXCR4 is expressed at low levels in bone marrow-resident neutrophils while almost undetectable on the surface of circulating neutrophils. 92 Interestingly, culture of human neutrophils for 20 hours triggers the For personal use only.…”
Section: Lymphatic Exit Of Neutrophilsmentioning
confidence: 99%